Teacher’s Strategies for Implementing TPACK in Teaching Writing: A Case Study at a Technical Vocational School in Malangbong - Yanti, Lisna; Said, Iskhak (Journal of English Education Program (JEEP), 2024)
This study was designed to find out the EFL Vocational School teacher’s implementation of TPACK and its dominant strategies implemented by EFL Vocational School teachers in teaching writing. This qualitative case study was conducted at a technical vocational school in Malangbong using observation, interviews, and documentation. Research participants were purposively recruited for this study including an English teacher at a technical vocational school in Malangbong. The results of this study showed that teacher has good knowledge about technological advances for teaching writing, especially in the aspects of CK, PK, PCK, TPK, and TPACK. Thus, an EFL teacher must have more concern on developing the TPACK framework of mind. Several problems emerged with its implementation including students' experiences with unsteady internet connections and electrical troubles, such as occasionally occurring in teaching activity that leads to pend or even cancel lessons, and it greatly disrupts the learning process. Concerning the challenges encountered by teachers, schools must always find out ways to solve problems in teaching and understand the concepts of the TPACK framework. Thus, teaching writing using the TPACK framework can be carried out effectively.